2016
DOI: 10.1088/0034-4885/79/6/064501
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance in Kondo lattice systems

Abstract: Nuclear magnetic resonance has emerged as a vital tool to explore the fundamental physics of Kondo lattice systems. Because nuclear spins experience two different hyperfine couplings to the itinerant conduction electrons and to the local f moments, the Knight shift can probe multiple types of spin correlations that are not accessible via other techniques. The Knight shift provides direct information about the onset of heavy electron coherence and the emergence of the heavy electron fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…We find no Knight shift anomaly at the 27 Al(4) site down to 5 K. This may be a consequence of the factor of three smaller hyperfine coupling at the 27 Al(4) as compared to 27 Al(3). It has been shown that the Knight shift anomaly nearly vanishes for H â in the Ce-115 systems [14]. So, it is probable that the anomaly is weak at the 27 Al(4) site for H ĉ and then vanishes for H â.…”
Section: Knight Shift Anomalymentioning
confidence: 99%
See 3 more Smart Citations
“…We find no Knight shift anomaly at the 27 Al(4) site down to 5 K. This may be a consequence of the factor of three smaller hyperfine coupling at the 27 Al(4) as compared to 27 Al(3). It has been shown that the Knight shift anomaly nearly vanishes for H â in the Ce-115 systems [14]. So, it is probable that the anomaly is weak at the 27 Al(4) site for H ĉ and then vanishes for H â.…”
Section: Knight Shift Anomalymentioning
confidence: 99%
“…In uncorrelated paramagnetic compounds, we expect the Knight shift to be proportional to the bulk magnetic susceptibility [32]. In Kondo lattice heavy fermion systems, there is a ubiquitous observation of deviation from this proportionality that has come to be associated with the formation of the coherent heavy electron fluid below the coherence temperature T * [14]. In the discussion below, we follow the literature and refer to the entire shift as the Knight shift.…”
Section: Knight Shift Anomalymentioning
confidence: 99%
See 2 more Smart Citations
“…CeRhIn 5 presents a unique opportunity to tune a highly correlated system between a diverse set of ground states, including unconventional superconductivity, local-moment magnetism, a putative (spin-or charge-) nematic, and a heavy Fermi liquid 8,13,21,22 . Here we chart the unknown territory of combined high field/high pressure, to serve as a testbed for theoretical approaches tackling this problem.…”
mentioning
confidence: 99%